COMPARATIVE STUDIES ON PHYSICOCHEMICAL PROPERTIES OF THE MINERAL SOILS IN THE MAJOR SAGO-PALM (METROXYLON SAGU ROTTB.)-GROWING AREAS OF EASTERN INDONESIA - Fransiscus Suramas Rembon; Yulius Barra Pasolon; Yoshinori Yamamoto; Tetsushi Yoshida (International Journal of Sustainable Tropical Agricultural Sciences (IJSTAS), 2014)
Physicochemical properties of the mineral soils, under major sago-palm-growing areas in the eastern Indonesia around Sentani near Jayapura, Papua Province (hereafter Jayapura); Kairatu, Seram Island, Maluku Province (Seram); Kendari, Southeast Sulawesi Province (Kendari); were studied and compared. The soil samples of 0-15 cm and 15-30 cm depth were collected from every site, respectively, from September 2005 to January 2008. The results revealed that the average of physicochemical properties of the soils from 0-30 cm depth in the sago-palm-growing areas varied depending on the site. Soil bulk densities were averagely higher in Seram (1.35 g cm-3) than those in Kendari (0.98 g cm-3) and Jayapura (0.89 g cm-3). Soil textures around Jayapura were dominated by silty loam. While in Seram soil texture was dominated by silty loam and loam, and around Kendari it was dominated by sandy loam, loam and silty clay. The averages of soil pHs were slightly acid (6.4) in Jayapura, acid in both Seram (5.5) and Kendari (4.9). Total carbons (total-C) in Kendari were higher (30.5 g kg-1) than those in Jayapura (27.2 g kg-1) and Seram (9.9 g kg-1). Based on the averages of nutrient contents including the CEC and the total-C, the sago-palm-growing areas showed the same trend in the order of Kendari > Jayapura > Seram in the CEC, total-N and total-C. On the other hand, the exchangeable-K, and the available-P were showed the trend in the order of Jayapura > Seram > Kendari. Variations of soil fertility such as the exchangeable-K, CEC, and total-N among the soils collected sites in each area are higher in the order of Kendari > Jayapura > Seram. And also we tried to discuss about the relation between the soil physicochemical properties and the reported growth parameters or starch productivity of sago palms grown on the same researched areas.